The love of neighbour in ancient Judaism : the reception of Leviticus 19:18 in the Hebrew Bible, the Septuagint, the Book of Jubilees, the Dead Sea Scrolls, and the New Testament - Akiyama, Kengo, 1985- (Leiden Brill, 2018)
"In The Love of Neighbour in Ancient Judaism, Kengo Akiyama traces the development of the mainstay of early Jewish and Christian ethics: "Love your neighbour." Akiyama examines several Second Temple Jewish texts in great detail and demonstrates a diverse range of uses and applications that opposes a simplistic and evolutionary trajectory often associated with the development of the "greatest commandment" tradition. The monograph presents surprisingly complex interpretative developments in Second Temple Judaism uncovering just how early interpreters grappled with the questions of what it means to love and who should be considered as their neighbour"--
The love command in Leviticus -- Leviticus 19:18 in the Septuagint and the Book of Jubilees -- Leviticus 19:18 in the Dead Sea Scrolls -- Leviticus 19:18 in the New Testament.
Based on author's doctoral thesis (University of Edinburgh, 2015) under the title: The 'love of neighbour' (Lev 19:18).
Includes bibliographical references (pages 217-245) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Golden rule; Neighborliness -- Religious aspects -- Judaism; Neighborliness -- Religious aspects -- Christianity; Love -- Religious aspects -- Judaism; Love -- Religious aspects -- Christianity